Fitness cost of malathion resistance in Egyptian Culex pipiens populations. Issue 3 (31st March 2022) - Elhawary, Noura A.; Soliman, Mohamed A.; Seif, Amal I.; Meshrif, Wesam S.
Abstract: The extensive use of insecticides in agriculture and public health has resulted in the rapid development of insecticide resistance in mosquito populations. Therefore, in this study, we aimed to evaluate insecticide resistance costs on the fitness of Culex pipiens . Two Cx. pipiens field populations (Beheira malathion‐resistant and Gharbia malathion‐susceptible) were compared to the reference (sensitive) population. The biochemical composition and expression of four genes relevant to insecticide resistance were estimated in third instar larvae. Adult survival, female fecundity and egg hatchability were also determined. As per our findings, it was found that the total protein and carbohydrate contents in Beheira malathion‐resistant larvae were significantly lower than that in the reference larvae. Beheira malathion‐resistant larvae had higher phenoloxidase (PO) specific activity than the reference population. In terms of the relevant genes, only cytochrome P450 (CYP6F1) expression showed elevated levels in the Gharbia malathion‐susceptible population compared to the Beheira malathion‐resistant population. In esterases (Estα and Estβ) and glutathione S‐transferase, the tested populations did not show any significant differences. Compared to the reference mosquito population, Gharbia malathion‐susceptible Cx. pipiens males exhibited significantly longer median survival. Female fecundity and hatchability showed nonsignificant differences among the populations tested. In conclusion, malathion resistance can induce lower protein and carbohydrate contents, but higher PO activity in larvae. Abstract : Malathion resistance induces lower protein and carbohydrate contents, but higher phenol‐oxidase activity in Culex pipiens field populations. Malathion resistance had no fitness cost in survival, female fecundity and egg hatchability. CYP6F1, Estα, Estβ and GST were not involved in malathion resistance in Cx. pipiens .